Aqueous colloidal processing of near-net shape B4C–Ni cermet compacts. Issue 8 (July 2016) - Rodríguez-Rojas, Fernando; Moreno, Rodrigo; Guiberteau, Fernando; Ortiz, Angel L.
Abstract: Aqueous colloidal processing was optimized for the environmentally friendly preparation of concentrated suspensions (29–40 vol.% solids loadings) suitable for the near-net shaping of B4 C + 16.6 vol.%Ni cermet compacts by slip casting. Specifically, on the basis of studies with dilute suspensions, it was confirmed that using very basic pHs (i.e., 10) is the key to ensuring the inertness and dispersibility of the Ni particles in water, and that deflocculant contents of at least ∼0.5 wt.% PKV and PAA are required to promote the colloidal stability of the B4 C and Ni particles, respectively. Concentrated B4 C + 16.6 vol.%Ni suspensions were consequently prepared at pH 11 with 1 wt.% PKV and PAA, and it was found that sonication for 1 min optimizes the rheological properties. Lastly, these concentrated suspensions were proven to be suitable for the slip casting of robust, highly-dense B4 C–Ni cermet compacts with near-net shape, whose green microstructures are very uniform, exhibit well-dispersed and packed particles, with no evidence of cracks or macrodefects, and with relative densities greater than 58% of the theoretical.